Croatian National Minorities in the Print Media - Mesić, MIlan; Bagić, Dragan (2005)
In contrast to the prevailing image of South Eastern Europe and Croatia itself that exists worldwide, our content analysis of the leading daily newspaper in the country does not prove that the print news media present national minorities in Croatia in a negative or derogative manner. The bulk of items dealing with minorities tends to be neutral and the rest can be evaluated as positive and disinterested rather than negative.
Projekt MZOS
ENG